Electronic Commerce: Theory and Practice - Margarita Išoraitė; Neringa Miniotienė (Integrated Journal of Business and Economics (IJBE), 2018)
Electronic commerce in the world is becoming an increasingly popular form of trade. Most shoppers start looking for products, descriptions and quality features online before buying a product. In order to provide customers with more convenience, more and more companies and existing stores are setting up their own online stores where a person can buy at a convenient time, even at night when regular stores are no longer working. Online stores allow you to save time spent by a person searching for a particular product and driving through shops. The article analyzes the concept of e-commerce, the advantages and disadvantages of electronic commerce, and the situation of electronic commerce in Lithuania.